MANAJEMEN PEMBENIHAN IKAN MAS (Cyprinus carpio) DI UNIT PELAKSANA TEKNIS (UPT) PENGEMBANGAN BUDIDAYA AIR TAWAR UMBULAN KABUPATEN PASURUAN, PROPINSI JAWA TIMUR - I’ah Zamzami; Prapti Sunarmi (Faculty of Science and Technology University Ibrahimy, 2013)
Carp is one of the freshwater fisheries sector commodities to growrapidly over time. This fish is much appreciated by the public because of the meat tasty. Carp is also a fish that is easy ti adapt to various environmental conditions so it is worth to be cultured. The purposeof thisstudytechnicalskillson themaintenance ofa hatchery techniques carp (Cyprinus carpio)which wasdone by observation, interviews, literaturesupportedthe active participationandsupport. This research was conducted in Freshwater Aquaculture Development Unit Umbulan Sidepan Village, District Winongan, Pasuruan, East Java Province from July to September 2012. Activities hatchery Carp include the selection and preparation of the parent, preparation of pond, water quality measurements, spawning, egg hatching, larval rearing, feeding, harvest and marketing. Spawning is done naturally by the ratio of male and female is 2:1. The number of eggs produced is 121.500 points and the survival rate of 60,01%. Profits earned in the amount of Rp. 6.634.980,- a year. Marketing of the Carp in the Pasuruan, Sidoarjo and Gresik.